Subject-loaded quadrifilar helical-antenna RF coil with high B1+ field uniformity and large FOV for 3-T MRI - Athalye, Pranav S.; Šekeljić, Nada J.; Ilić, Milan M.; Tonyushkin, Alexey A.; Notaroš, Branislav M. (Concepts in magnetic resonance. Part B, Magnetic resonance engineering, 2016)
A novel method for excitation of RF B1 field in high‐field (3‐T) magnetic resonance imaging (MRI) systems using a subject‐loaded quadrifilar helical antenna as an RF coil is proposed, evaluated, and demonstrated. Design, analysis, characterization, and evaluation of the novel coil when situated in a 3‐T MRI bore and loaded with different phantoms are performed and cross‐validated by extensive numerical simulations using multiple computational electromagnetics techniques. The results for the quadrifilar helical‐antenna RF body coil show (a) strong field penetration in the entire phantoms; (b) excellent right‐hand circular polarization (RCP); (c) high spatial uniformity of RCP RF magnetic field, B1+, throughout the phantoms; (d) large field of view (FOV); (e) good transmit efficiency; and (f) low local specific absorption rate (SAR). The examples show that the new RF coil provides substantially better B1+‐field uniformity and much larger FOV than any of the previously reported numerical and experimental results for the existing RF coil designs at 3 T in literature that enable comparison. In addition, helical RF body coils of different lengths can, for instance, easily provide an excellent RCP and highly uniform B1+‐field within the MRI maximum FOV length of 50 cm, and even 100 cm. The proposed MRI RF coil yields a remarkable improvement in the field uniformity in the longitudinal direction, for various phantoms, with comparable efficiency and SAR levels.